Biological Activities and Application of Chitosan Compound in Various Human Diseases - Qarina Hasyala Putri (Jurnal Kesehatan Amanah, 2024)
Chitosan is a biopolymer derived from chitin that undergoes a deacetylation process. Chitin that is sold commercially comes from crustacean shells such as oysters and crabs. In addition, chitin can also come from fungi, insects, molluscs and algae that are given a strong alkali solution to produce chitosan. Chitosan is one of the biopolymers that has many biological activities. Because of its diverse biological activities, chitosan is widely developed for applications in the health sector. This article will discuss what biological activities chitosan has and its developing applications.